STRATEGI PENDAMPINGAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (P2TP2A) TERHADAP ANAK KORBAN KEKERASAN SEKSUAL DI KABUPATEN MERANGIN - Nanik Istianingsih dan Fina Afriany (Normative Jurnal Ilmiah Hukum, 2020)
Cases of violence against men, women, and even children often make headlines in various media. However, many cases have not been revealed, because this violence case is considered as an insignificant matter, especially the problem of violence against children. So many cases of violence that occur in children but only a few cases that are followed up. In Merangin District, Jambi Province cases of violence have increased in recent years. The purpose of this study was to determine the assistance strategy for the Integrated Service Center for Women's Empowerment and Child Protection (P2TP2A) for children victims of sexual violence in Merangin District. The sample in this study amounted to 8 people who are informants who are in direct contact with programs and cases of violence against children. This type of research is descriptive qualitative with data analysis techniques using data triangulation. The results of the study found that in handling cases of violence against children the Integrated Service Center for Women's Empowerment and Child Protection (P2TP2A) was in accordance with standard operating procedures stipulated by the State Ministerial Regulation for Women Empowerment and Child Protection Number 5 of 2010. In carrying out the assistance of P2TP2A officers also has a strategy implemented for handling cases. However P2TP2A officers still encountered obstacles including difficulty in communication from the family and the lack of facilities, especially shelter or safe houses for victims of violence against children. So the suggestion from this research is that the victim's family should be more open to P2TP2A officers so that violence cases can be resolved properly. And the government should provide shelter facilities or safe houses for victims of violence.